Contribution of brand image to consumer behavior: a systematic review - Barrueta-Pinto, Mark (2024)
Objective. The contribution of brand image to consumer behavior is explored, since, in the business world, the impact of reputation on consumers with respect to the company's brand can determine the success or decline of an organization. Methodology. The approach is based on a solid qualitative documentary analysis. The PRISMA methodology is applied. Which involves an exhaustive search of the relevant literature, followed by the evaluation of the sources for the development of the work. Results and Discussion. Twenty-two articles published in high impact journals were obtained. Multiple interpretations and considerations on the concept of consumer behavior, as well as brand image, stand out. However, a common conception of consumer behavior refers to the perception of habits, lifestyles, attitudes and practices. Implications of the research. The implications of this research suggest that, despite the diversity of perspectives on consumer behavior, there is a general consensus that this concept relates to the perception of habits, lifestyles, attitudes and practices. Originality/value: The study does not limit itself to a single definition, but explores the various interpretations and considerations of the concept, revealing the complexity and richness of the field. The lack of a single definition of the concept implies the need for further research to delimit and deepen the understanding of consumer behavior in different contexts.